ANALISIS PERAN PERBANKAN DAN INKLUSI KEUANGAN DALAM MENGEMBANGKAN POTENSI PARIWISATA DI KABUPATEN SUMENEP - Machrus Rahman Trianto; Aprilina Susandini (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
Nowadays, tourism development plays an important role in advancing a region and requires capital, especially from financial institutions which play an important role as channelers of funds. The relevance of regional banking inaa country's economic growth and development cannot be overstated. Sumenep Regency has beautiful natural topography and a diversity of traditions and culture so that the existence of the tourism sector can contribute to increasing Regional Original Income (PAD). In this case, capital support, especially from banking financial institutions, is very necessary. Apart from that, financial inclusion issan important thing for the government to pay attention to, because it is an effort to encourage the financial system to be accessible to all levels of society. This research method is quantitative. It is hoped that this research can provide a better understanding of how increasing awareness of financial inclusion and the role of banking in tourism can help in national economic recovery and development. The results of this research are that theevariables partially have a significant effect on tourism development and the partial financial inclusion variable does not have a significant effect on the decision.to.visit. Banking and financial inclusion simultaneously influence tourism development.